(untitled) (Itinera, 2022)
Can we measure the experiences of physical and VR art installations? How could that be done? The present research attempts to answer these questions through the use of a multimethod approach to assess every dimension of the experience of art. Wristband and questionnaires have been used as research tools to understand how the experience of art installations in the museum takes place and to study it, through and across two different installations. To examine art experiences in an ecologically valid setting, a pop-up lab was used at the Frankfurter Kunstverein, creating an opportunity to reach the «golden path» for empirical investigation of art experiences and, in the present instance, specific experience of art installations. Two installations have been selected from the exhibition «The Intelligence of Plants» (16.10.2021 – 20.02.2022) as single-cases to explore a suitable methodology for the experience of art installations. Both installations were chosen by the curator Franziska Nori for their shared goal of connecting the observers’ bodies with the ones of the giant trees featured in both installations, in order to look for commonalities with other non-human fellow beings. Additionally, both these installations aim at evoking experiences of the sublime in the audience. Sensations, emotions, and thoughts, as well as physiological reactions and movements, partake in these experiences. Data collected with the presented methodology is potentially very rich thanks to the presence of original art installations (rather than their reproductions) over the space and time they are meant to be visited. Data from the questionnaires can be considered ecologically valid, as consisting of accurate subjective reportages of the visitors while actually experiencing the installations in situ. The proper measurement of physical and behavioral patterns is however harder to achieve as it relies on biometrics in a real-world setting. To overcome this issue and have more control over the multiple variables that can affect the measurements, a collaboration among disciplines and professionals from the art sector is at the heart of the matter.